Transport Network Vehicle System – Human Resources 2 (Competency Management, Training Management, Learning Management, Employee Self-Service, Succession Planning): Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Transport Network Vehicle System is a popular transportation method commuters use today, often through companies such as Grab or Uber. Human Resource 2 manages employee evaluations, promotions, exams, training, and service. This study aims to solve Competency, Succession Planning, Training, Learning, and Employee Self-Service issues. The agile development methodology consists of six phases. The first phase determines the software's objectives and scope. Prototyping may be included in the design phase. The software design is then translated into source code in the second phase. Testing starts in the fourth phase after coding and releasing modules. The fifth phase involves deployment, making the application available to users. The final phase involves client feedback evaluation. This method often uses sprints, which are incremental and iterative work sequences. The Scrum masters and team conduct interviews, plan the project and business processes and create a product backlog. They are also responsible for the system's design, coding, development, discovery, integration, testing, and implementation.